Production, Distribution, and Consumption: Extending Studies of Racialized Media beyond Racial Representations. Issue 1 (February 2020) - Gonzalez-Lesser, Emma; Hall, Rhys; Hughey, Matthew W.
The recent 2016 presidential campaign season and subsequent presidency has created a context in which the general public is looking deeper into the "behind the scenes" influences on the media. Of particular interest has been "fake news" and the biases of various news media outlets. These "behind the scenes" actions occur at production (the encoded ideological meanings and narratives, the material structures, the people involved, and global political economy of media), distribution (marketing strategies, gatekeeping practices, laws and policies, and media-industry customs), and consumption (reception and interpretation by media audiences). In this introduction to our special issue, we outline the relevance of examining these extra-representational processes of racialized media, particularly in today's climate.